O cuidado fisiogerontológico domiciliar - Freddi, Fabiana (2010)
The object of this research is the physio-geriatric home care. During the last decades we can observe a large aging population worldwide. This theme was developed from the need to report the clinical experience in home physical therapy home care for elderly patients. The objective of this study is to understand the importance of the physio-geriatric care has on the lives of senior citizens at home in the city of São Paulo. To this end, we used the approach to clinical research through a qualitative field research. The participants are 8 elderly over the age of 70 years (which were: 2 men and 6 women). The procedure of the research involved the collection of testimonies of individuals selected in their homes during the year 2009. This process was carried out by observation and open interviews semi-structured in the form of narratives written in free speech. The results revealed that the importance of this type of intervention is related to the physical benefits gained by older body, but the fact remains that the physio-care geriatric home beyond the simple trade professionals and end extending over a long period time, establishing,a relationship of growth and development with regard to respect, dedication and affection